The impact of surface air leakage on coal spontaneous combustion hazardous zone in gob of shallow coal seams: A case study of Bulianta Mine, China. (1st July 2021) - Zhuo, Hui; Qin, Botao; Qin, Qinghe
Highlights: The effect of surface air leakage on the hazardous zone of coal spontaneous combustion in the shallow coal seams gob is studied by simulation. The coal spontaneous combustion dangerous zone in the overlying gob is mainly controlled by surface air leakage. The coal spontaneous combustion hazardous zone of lower coal seam gob is mainly controlled by the air leakage from the working face, but the surface air leakage will affect its the location and area. Abstract: Determining the coal spontaneous combustion hazardous zone is of great significance to the fire prevention and extinguishing work of the gob. In this paper, considering the actual situation of the residual coal in the gob of the Bulianta Mine, a spontaneous combustion characteristics test of the water immersion coal (S180 ) and raw coal (S0 ) was carried out. According to the experimental results, and considering the air leakage from surface cracks, a three-dimensional model of coal spontaneous combustion in shallow coal seams gob is established, and the correctness of the model is verified by on-site measured data. Then, the model is used to study the effect of different surface air leakage conditions on the hazardous zone of coal spontaneous combustion in the gob of shallow coal seams. Surface air leakage volume increased from 0% to 12% of the working face air volume, and the maximum oxygen concentration in the overlying gob increase of nearly 30 times; the maximum wind velocity increase of 14 times. Even so, there is no coal spontaneous combustion hazardous zone that satisfies both wind velocity and the oxygen concentration in the overlying gob. In the gob of the lower coal seam, with the increase of surface air leakage, coal spontaneous combustion hazardous zone move to the air intake side and deep part of the gob, the maximum width gradually increases; and area increases first, then decreases, which has a quadratic functional relationship with the surface air leakage.